Πειραματική απόδειξη της συνεισφοράς του CO2 στο φαινόμενο του θερμοκηπίου - Θεοφάνους, Θάλεια (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος ,Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
The Bachelor thesis at hand entitled Experimental Evidence of the Contribution of CO2 on the Greenhouse Effect aims to investigate through experimentation the contribution of CO2 in global warming. The first chapter entitled Theory refers to the physicochemical properties of CO2, the natural and anthropogenic sources of CO2 and the problems caused to the environment and humans. The European legislative framework regarding CO2 emissions is also described, and ways of its reduction or removal from the atmosphere. In the second chapter entitled Literature Review refers to the methods used to measure the concentration of CO2 and temperature from million years ago until the present and the correlation between them. In addition, there are cited views of the scientific community, which is divided concerning the causes of climate change. The third chapter entitled Experimental, describes the experimental procedure followed to simulate conditions in the lower atmosphere in the two boxes constructed for the needs of the experimental procedure. These boxes are made of plexiglass with a provision of CO2 at various concentrations in one of the two boxes, for drawing conclusions regarding the correlation of temperature and CO2. The fourth chapter entitled Results – Discussion presents the results of the experimental procedure and the results of calculations regarding the time horizon of depletion of proven global fossil fuel reserves and the amount of CO2 that will be released into the atmosphere by their combustion. Experimental results showed that there is a logarithmic relationship between CO2 concentration and induced increase of temperature. Today, the average concentration of CO2 in the atmosphere is 391 ppm. According to the results of the experimental procedure, an input concentration of 450 ppm CO2 (0,045% concentration in the atmosphere) will rise the temperature 0,4ºC while increasing the concentration of CO2 up to 1% will cause a rise in temperature of 1,2ºC. Apart from the experiments reported here, calculations were made regarding the increase of CO2 concentration in the atmosphere by combusting all proven global reserves of fossil fuels. It was also calculated the estimated time in which the depletion of these reserves will take place and therefore the release of CO2 into the atmosphere by their combustion. Furthermore, based on the calculations made in this Diploma Thesis, vi Abstract vii depletion of fossil fuels is expected to take place in 70 years from today (2082). According to the logarithmic equation calculated, from the combustion of all the fossil fuels the additional concentration of CO2 in the atmosphere will be 298 ppm and will cause an increase of 0,145ºC of the temperature, above current levels. Increasing the concentration of CO2 in the atmosphere by combusting fossil fuels will activate feedback mechanisms that will cause further warming. Finally, the fifth chapter entitle Conclusion – Future Research, presents the conclusions derived from the experimental procedure as well as suggestions for future improvement of the experiment.
Keywords: Greenhouse; Atmosphere; Θερμοκήπιο; Ατμόσφαιρα